PEMBERDAYAAN KELOMPOK WANITA TANI TIRTA RAHAYU MELALUI PENGUATAN DIGITAL MARKETING PRODUK OLAHAN KREATIF HASIL PERTANIAN BERBASIS IPTEK - Beta Asteria; Sulastiningsih Sulastiningsih; Muhammad Subkhan; Rafif Raditya Muhrizal; Dimas Rizky Kurniawan (Universitas Mataram, 2026)
The Tirta Rahayu Women's Farmers Group (KWT) in Tamanan Village, Banguntapan District, Bantul Regency, has great potential to process agricultural products into value-added products. However, limited marketing access is a major challenge in business development. Strengthening digital marketing is a strategic solution to increase the competitiveness and sustainability of the KWT business. A Science and Technology (IPTEK) approach is crucial to support marketing transformation into the digital era. This activity aims to increase the capacity of KWT members in utilizing digital platforms and expanding market reach through technology-based marketing strategies. The implementation method included training, workshops, and direct mentoring in the use of social media, e-commerce, and digital marketing tools, which took place over four sessions. Quantitative data showed a significant change, with participants' average scores jumping from 50-70 to 75-90 after participating in the empowerment program through digital marketing reinforcement. The training materials also covered branding and market analysis. These activities resulted in an increased understanding of digital marketing strategies among KWT members. Processed products such as vegetable chips, healthy juices, vegetable packages, and vegetable nuggets began to be marketed online through social media and marketplaces. Sales showed a significant increase, and the market network expanded beyond the region. The activities also strengthened the role of women in the digital economy. The spirit of collaboration and innovation also increased among KWT members. This program provides a strong foundation for future sustainable business development. Conclusions: The digital marketing reinforcement activities have proven effective in increasing KWT capacity, marketing, and income. This program is worthy of replication in other farmer groups.